Aplikasi Computer Based Test (CBT) Berbasis Website Menggunakan Metode RAD Pada SMA Negeri 21 Medan - Hutahaean, Maxi Lamtama; Hadinata, Edrian; Faradillah, Yanty (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2025)
A Computer-Based Test (CBT) can be utilized as a method that leverages technology in the field of education, packaged in a manner that is both effective and efficient. At SMA Negeri 21 Medan, the examination process is still conducted manually using a Paper-Based Test (PBT). The academic staff and students at SMA Negeri 21 Medan still use paper for everything from writing the exam questions to administering the exams, leading to inefficiencies in cost, time, and errors in the grading process that can disadvantage the students. This research aims to design and develop a computer-based test (CBT) application, beginning with data collection methods (literature review, interviews, and observations) and using the Rapid Application Development (RAD) system development methodology. The system design was created using UML, with use case diagrams, activity diagrams, sequence diagrams, and class diagrams. The resulting system can assist teachers and other academic staff in the online examination process, where the scores will be automatically generated once the exam is completed, thereby saving time from manually grading each exam. The application also includes a QR code containing student data to assist academic staff in checking whether students have paid their tuition and exam fees. The application system testing was conducted using the black box testing method to determine the functionality of the application according to the requirements.